Full-biodegradable ultrahigh-barrier antibacterial coating and use method thereof
By applying recycled cellulose and ZNO nanoparticles on paper -based packaging materials to solve the problem of cumbersome and high costs in existing technology, achieve efficient, economic blocking and antibacterial effects, suitable for industrialization, suitable for industrialization Production.
Patent Information
- Application Number
- CN202411123869.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-01-28
AI Technical Summary
The existing technology for preparing barrier coatings for bio-based polymers is complicated to prepare, the coating amount is large or catalytic reaction is required, which leads to high production costs, high operational difficulties and difficult to achieve industrial production.
Ultra-high-resistance antibacterial coating composed of recycled cellulose and Zno nanoparticles is used to transfer cellulose fiber to the surface of the base paper by dissolving-regeneration process in different concentrations of ZNCL2 solution, combined with ZNO nanoparticles that grow in situ. Form the coating of dense structures.
The efficient and simple coating process has been realized, the production cost is reduced, the blocking performance, antibacterial performance and degradability of paper -based packaging materials are improved, and it is suitable for industrialized production.
Smart Images

Figure CN119372953A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of paper coating in the papermaking industry, and specifically relates to a fully biodegradable ultra-high barrier antibacterial coating and a use method thereof. Background Art
[0002] At present, petroleum-based synthetic plastics and metal materials such as aluminum foil are often used as key barrier materials in paper-based packaging materials. On the one hand, plastics are non-renewable and non-degradable, and long-term use will have serious impacts on human health and the ecological environment. On the other hand, plastic or metal components as barrier layers in paper-based packaging containers make recycling difficult and increase the overall recycling cost.
[0003] Bio-based polymers such as polysaccharides (chitin, chitosan, cellulose and starch, etc.), lipids (beeswax, free fatty acids) and proteins have many advantages, such as being renewable, biodegradable, safe and non-toxic, and biocompatible. They can be used to prepare barrier coatings through appropriate technical means, and thus have broad application prospects in the field of paper-based packaging. Patent CN 111172805A discloses a method for preparing a biomass-based barrier coating, which mainly uses microfibrillated cellulose as the main raw material and is combined with biomass adhesives, rheology modifiers and pigment dispersions to prepare barrier coatings and apply them to the surface of paper to give them good barrier properties. Patent CN 116676812 B discloses a chlorine-free reinforced food packaging paper, which mixes maleic anhydride acylated chitosan, modified konjac glucomannan, nanocellulose, polyvinyl alcohol fiber and polyethyleneimine to obtain a coating sizing solution, which is then applied to the surface of base paper to obtain a reinforced coating to obtain good barrier properties and mechanical properties. Patent CN 117626703A discloses a degradable composite barrier coating applied to paper-based materials, which is prepared by dissolving polyvinyl alcohol (PVA1799) in N, N-dimethylformamide (DMF) and adding preservatives, concentrated hydrochloric acid, poly-β-hydroxybutyrate (PHB) and isophorone diisocyanate (IPDI) to obtain a composite barrier coating, which can improve the gas barrier properties of packaging films. Patent CN114867912B discloses a biopolymer composition and its use as a powder coating, which is mainly formed by the esterification reaction product of a biodegradable polyester and a metalloxane precursor, and can provide barrier properties for packaging materials after forming a coating on a substrate.
[0004] The currently disclosed technology of using bio-based polymers to prepare barrier coatings for use in paper-based packaging materials often has complicated coating preparation, large coating amounts or requires catalytic reactions to obtain, high production costs, greater operating difficulty, and poor feasibility of industrial production. Summary of the invention
[0005] In view of the defects and shortcomings of the prior art, the object of the present invention is to provide a fully biodegradable ultra-high barrier antibacterial coating to meet the requirements of paper-based packaging materials for barrier properties, degradability, antibacterial properties and recyclability.
[0006] Another object of the present invention is to provide a method for using a fully biodegradable ultra-high barrier antibacterial coating, which is suitable for coated base papers of various specifications and models, is simple and easy to operate, and is fully compatible with existing industrial coating technologies and equipment.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A fully biodegradable ultra-high barrier antibacterial coating, the content of each component, by mass percentage: 95-99.5% regenerated cellulose, 0.5-5% ZnO nanoparticles. The regenerated cellulose is made of dissolving pulp fibers by mixing with ZnCl at different concentrations. 2 The dissolution-regeneration behavior in the solution is transferred to the surface of the base paper, and the ZnO nanoparticles are Zn 2+ During the regeneration process of cellulose, ZnO nanoparticles are uniformly embedded in the regenerated cellulose membrane through in situ growth.
[0009] The technical principle and effect of this technical solution are:
[0010] Cellulose is a linear polysaccharide composed of glucose structural units connected by β-1,4-glycosidic bonds and arranged into neat bundle structures. Due to the presence of intramolecular and intermolecular hydrogen bonds, cellulose fibers are not easily dissolved in conventional solvents and cannot be processed by melt processing.
[0011] ZnCl 2 Molten salt hydrate represented by is a highly concentrated inorganic salt solution. Its application as a non-derivatized solvent for cellulose has the characteristics of high dissolution efficiency, mild conditions, low cost and easy recovery. 2 When the mass fraction of the solution exceeds 65%, Zn 2+ It will not be completely saturated with water molecules. After adding dissolving pulp fibers, the Zn in the solution that is not saturated with water molecules 2+ The ZnCl2+ forms a coordination bond with the oxygen atoms on the hydroxyl groups in the cellulose molecules, which breaks the original hydrogen bond network between and within the cellulose molecules, causing the dissolving pulp fibers to gradually dissolve, thus forming a uniform and transparent ZnCl2+ 2 / cellulose / water solution. When a certain amount of water is added to the above uniform and transparent solution, the Zn bonded to the oxygen atom on the hydroxyl group of the cellulose molecule 2+The cellulose fibers will gradually combine with excess water molecules to form hydrates, and the released oxygen atoms will re-form hydrogen bond networks between and within cellulose molecules, thereby leading to the formation of regenerated cellulose. The present invention transfers the dissolution-regeneration process of the cellulose fibers to the surface of the base paper through a simple, efficient and easy-to-operate coating method. Specifically, the uniform and transparent ZnCl 2 The / cellulose / aqueous solution is transferred to the surface of the base paper through coating technology and then dried. After that, it is simply washed and dried to achieve the regeneration of cellulose fibers on the surface of the base paper, thereby forming an ultra-thin regenerated cellulose film with a physically dense structure on the surface of the base paper.
[0012] The present invention selects ZnCl 2 Molten salt hydrate is used as a green solvent for dissolving cellulose, mainly because ZnO nanoparticles will be evenly deposited on the regenerated cellulose film during the cellulose regeneration process, giving the regenerated cellulose film higher barrier properties and certain antibacterial properties. 2 Part of Zn in solution 2+ It can react with the hydroxyl groups on regenerated cellulose and finally deposit in the form of ZnO nanoparticles. The number and position of the exposed active hydroxyl groups on regenerated cellulose and the free Zn 2+ The number and location of the formed ZnO nanoparticles are determined by the fact that the active hydroxyl groups on the regenerated cellulose membrane are evenly distributed on the regenerated cellulose membrane, and the number of active hydroxyl groups and the free Zn 2+ It determines the uniform deposition of ZnO nanoparticles during the formation of regenerated cellulose. Due to the nano-size effect of ZnO nanoparticles, the transmission path of small mass transfer molecules such as water molecules, oxygen molecules, carbon dioxide molecules, etc. is extended, thereby giving the regenerated cellulose film a higher barrier property; in addition, ZnO nanoparticles react with water molecules to produce hydroxyl radicals, and two hydroxyl radicals can combine to form a bactericide, hydrogen peroxide. Hydrogen peroxide molecules can penetrate into bacterial cells and cause their death. Therefore, ZnO nanoparticles have antibacterial properties, thereby giving the regenerated cellulose film certain antibacterial properties. The present invention innovatively utilizes ZnO nanoparticles to form a uniform deposition in the regenerated cellulose film by in-situ growth, and utilizes the nano-size effect and antibacterial properties of ZnO nanoparticles to give the functional coating of the present invention a higher barrier property and certain antibacterial properties.
[0013] This technical solution uses dissolving pulp fibers and innovatively uses different coating technologies to transfer the physical process of dissolution-regeneration of dissolving pulp fibers in ZnCl2 solutions of different concentrations to the surface of base paper. At the same time, the regular crystalline structure of regenerated cellulose and ZnO nanoparticles formed by in-situ regeneration are used to form a densely structured, fully biodegradable, functional coating with barrier and antibacterial properties on the surface of the base paper.
[0014] Furthermore, the dissolving pulp fiber is one of bleached coniferous or hardwood kraft dissolving pulp, bleached bamboo dissolving pulp or cotton dissolving pulp. Preferably, the degree of polymerization DP of the dissolving pulp fiber is 200-700, and the α-cellulose content is greater than 95%.
[0015] Furthermore, the ZnCl 2 The ZnCl solution is analytically pure and has an active ingredient content of ≥98%. 2 The mass fraction of the solution is 65-80%.
[0016] Furthermore, the particle size of the in-situ grown ZnO nanoparticles is 80 to 160 nm.
[0017] The present invention also provides a method for using a fully biodegradable ultra-high barrier antibacterial coating, comprising the following steps:
[0018] (1) Weigh 65-80 parts of ZnCl 2 The solid and 20-35 parts of ionized water are fully stirred until ZnCl 2 Completely dissolved to obtain ZnCl 2 Solution;
[0019] (2) Weigh 0.5 to 3 parts of dissolving pulp fiber and the prepared ZnCl 2 The solutions are mixed, stirred rapidly at a certain temperature until completely dissolved, and then cooled to obtain ZnCl 2 / cellulose / aqueous solution;
[0020] (3) ZnCl 2 / cellulose / aqueous solution based on ZnCl 2 The above ZnCl 2 / cellulose / water solution transfer to different base paper surfaces;
[0021] (4) Base paper is treated with ZnCl 2The / cellulose / aqueous solution is allowed to stand for a certain period of time after coating, and then immersed in deionized water for 30 to 120 seconds to regenerate and desalinate the dissolved cellulose pulp, and finally dried by a drum drying method or a flat plate drying method, the drying temperature is 85 to 105° C., and the drying time is 10 to 30 minutes, so as to obtain a paper-based material with an ultra-high barrier antibacterial coating on the surface.
[0022] Furthermore, in step (2), the dissolution temperature of cellulose is 70-100°C and the dissolution time is 1-10 minutes. When preparing a high-concentration cellulose solution, heating is stopped after every 10 seconds, and the heating is repeated multiple times until the dissolving pulp fibers are completely dissolved.
[0023] Further, in step (3), as ZnCl 2 As the mass fraction of the solution increases, the viscosity of the cellulose solution system increases sharply. Preferably, when ZnCl 2 When the mass fraction of the solution is 65-70%, spin coating or rod coating can be used; when ZnCl 2 When the mass fraction of the solution is 70-80%, a scraper coating process can be used; preferably, the coating amount of the regenerated cellulose coating is 0.2-3 g / m 2 .
[0024] Further, in step (4), the base paper is treated with ZnCl 2 The / cellulose / aqueous solution is allowed to stand after coating so that the cellulose solution can penetrate into and fill the pores on the surface of the base paper, thereby improving the barrier effect of the regenerated cellulose coating. Preferably, the standing time is 5 to 10 minutes.
[0025] Furthermore, in order to achieve better antibacterial performance, the ultra-high barrier antibacterial coating on the surface of the base paper contains 0.5-5% ZnO nanoparticles by mass, with a particle size of 80-160 nm.
[0026] Compared with the prior art, the present invention provides a fully biodegradable ultra-high barrier antibacterial coating and a method of using the same. The active ingredients of the ultra-high barrier antibacterial coating are regenerated cellulose and ZnO nanoparticles, which have good compatibility with base paper materials and high interface bonding strength. While playing a barrier role, it can also effectively improve the mechanical strength and antibacterial properties of paper. The ultra-high barrier antibacterial coating is applicable to but not limited to a variety of coated base papers such as thin paper, cardboard and corrugated paper. The barrier coating is fully biodegradable, non-toxic and harmless to the environment, has a simple preparation process, is easy to use, and is fully compatible with existing industrial coating technology and equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the structure of a fully biodegradable ultra-high barrier antibacterial coating
[0028] Figure 2 A method for using a fully biodegradable ultra-high barrier antibacterial coating DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments to help those skilled in the art have a more complete, accurate and in-depth understanding of the inventive concept and technical solution of the present invention. It should be understood that the accompanying drawings and the following embodiments are only used to illustrate the present invention, rather than to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the protection scope of the present invention. The specific process parameters, etc., of the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range based on the description herein, and are not limited to the specific values exemplified below.
[0030] In the description of the present invention, it should be noted that, if no specific conditions are specified in the examples, the experiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.
[0031] The invention provides a fully biodegradable ultra-high barrier antibacterial coating, which comprises the following components by mass percentage: 95-99.5% of regenerated cellulose and 0.5-5% of ZnO nanoparticles.
[0032] Specifically, the regenerated cellulose is prepared by dissolving pulp fibers in different concentrations of ZnCl 2 The dissolution-regeneration behavior in the solution was transferred to the base paper surface. The ZnO nanoparticles were ZnCl 2 / Cellulose / Cellulose in aqueous solution is uniformly deposited and embedded in the regenerated cellulose membrane through in situ growth during the regeneration process.
[0033] Specifically, the dissolving pulp fiber is one of bleached coniferous or hardwood kraft dissolving pulp, bleached bamboo dissolving pulp or cotton dissolving pulp, the degree of polymerization DP of the dissolving pulp fiber is 200-700, and the α-cellulose content is greater than 95%.
[0034] Specifically, the ZnCl 2 The ZnCl solution is analytically pure and has an active ingredient content of ≥98%. 2 The mass fraction of the solution is 65-80%.
[0035] Specifically, the particle size of the ZnO nanoparticles grown in situ in the regenerated cellulose is 80 to 160 nm.
[0036] A method for using a fully biodegradable ultra-high barrier antibacterial coating of the present invention comprises the following steps:
[0037] (1) Weigh 65-80 parts of ZnCl 2 The solid and 20-35 parts of ionized water are fully stirred until ZnCl 2 Completely dissolved to obtain ZnCl with a mass concentration of 65-80% 2 Solution;
[0038] (2) Weigh 0.5 to 5 parts of dissolving pulp fiber and the prepared ZnCl 2 Mix the molten salt hydrate, stir rapidly at 70-100°C for 1-10 minutes until completely dissolved, and cool to obtain ZnCl 2 / cellulose / aqueous solution;
[0039] (3) ZnCl 2 / cellulose / aqueous solution based on ZnCl 2 When the mass fraction of ZnCl 2 When the mass fraction of the solution is 65-70%, spin coating or rod coating can be used; when ZnCl 2 When the mass fraction of the solution is 70-80%, a scraper coating process can be used; preferably, the coating amount of the regenerated cellulose coating is 0.2-3 g / m 2 . ;
[0040] (4) Base paper is treated with ZnCl 2 The / cellulose / aqueous solution is allowed to stand for 5 to 10 minutes after coating, and then immersed in deionized water for 30 to 120 seconds to regenerate and desalinate the dissolved cellulose pulp, and finally dried by drum drying or flat plate drying at a temperature of 85 to 105° C. for a drying time of 10 to 30 minutes to obtain a paper-based material with an ultra-high barrier antibacterial coating on the surface.
[0041] Example 1
[0042] A fully biodegradable ultra-high barrier antibacterial coating comprises the following components by mass percentage: 99.5% of regenerated cellulose and 0.5% of ZnO nanoparticles.
[0043] The method of use specifically includes the following steps:
[0044] (1) Weigh 65 parts of ZnCl 2 The solid and 35 parts of deionized water were stirred thoroughly until ZnCl 2 Completely dissolved to obtain 65% ZnCl 2 Solution;
[0045] (2) Weigh 0.5 parts of bleached softwood kraft dissolving pulp fiber with a DP of 210 and an α-cellulose content of 96.9% and mix with the prepared ZnCl 2The solutions were mixed and stirred rapidly at 80°C for 15 min until completely dissolved. After cooling, a flowable, translucent ZnCl solution with a 0.5% cellulose content was obtained. 2 / cellulose / aqueous solution;
[0046] (3) Commercially available 70g / m 2 The base paper is coated with a scraper on a flat coater to coat the ZnCl 2 / cellulose / water solution is transferred to the surface of the base paper, and the coating amount is controlled to be 0.2g / m 2 ;
[0047] (4) Base paper is treated with ZnCl 2 The / cellulose / aqueous solution was allowed to stand for 5 minutes after coating, and then immersed in deionized water for 60 seconds to regenerate and desalinate the dissolved dissolving pulp cellulose on the surface of the base paper, and then dried by drum at 85°C for 20 minutes to obtain a paper-based material with an ultra-high barrier antibacterial coating on the surface.
[0048] Example 2
[0049] The composition of a fully biodegradable ultra-high barrier antibacterial coating is the same as that of Example 1.
[0050] In the specific operation steps of the method of use, the amount of dissolving pulp cellulose in step (2) is changed from 0.5 parts to 1.0 parts; the coating amount in step (3) is changed from 0.2 g / m 2 Changed to 1.0g / m 2 ; The remaining steps are the same as in Example 1.
[0051] Example 3
[0052] A fully biodegradable ultra-high barrier antibacterial coating comprises the following components by mass percentage: 99.0% of regenerated cellulose and 1.0% of ZnO nanoparticles.
[0053] In the specific operation steps of the method of use, in addition to the ZnCl prepared in step (1), 2 The mass fraction of the solution was changed from 65% to 68%; the bleached softwood kraft dissolving pulp fiber with a DP of 210 and an α-cellulose content of 96.95% in step (2) was changed to a bleached bamboo dissolving pulp fiber with a DP of 416 and an α-cellulose content of 96.2%; the base paper in step (3) was changed from a commercially available 70 g / m 2 Coated base paper changed to self-made 30g / m 2 Lightweight paper; the coating method was changed from one-time coating on a flat coater using a doctor bar to coating using a spin coating method; the coating amount was changed from 0.2g / m 2 Changed to 1.0g / m2 ; The soaking time in deionized water in step (4) was changed from 60S to 90S; the drying temperature was changed from 85°C to 90°C; the remaining operating steps were the same as in Example 1.
[0054] Example 4
[0055] The composition of a fully biodegradable ultra-high barrier antibacterial coating is the same as that of Example 1.
[0056] The specific operation steps of the method of use are as follows: in step (2), the bleached softwood kraft dissolving pulp fiber with a degree of polymerization (DP) of 210 and an α-cellulose content of 96.95% is replaced with a bleached bamboo dissolving pulp fiber with a degree of polymerization (DP) of 635 and an α-cellulose content of 96.8%; in step (3), the base paper is replaced with a commercially available 70 g / m 2 Coated base paper changed to self-made 30g / m 2 Lightweight paper; the coating method was changed from one-time coating on a flat coater using a doctor bar to coating using a spin coating method; the coating amount was changed from 0.2g / m 2 Changed to 1.5g / m 2 ; The remaining steps are the same as in Example 1.
[0057] Example 5
[0058] A fully biodegradable ultra-high barrier antibacterial coating comprises the following components by mass percentage: 95.0% of regenerated cellulose and 5.0% of ZnO nanoparticles.
[0059] In the specific operation steps of the method of use, in addition to the ZnCl prepared in step (1), 2 The mass fraction of the solution was changed from 65% to 80%; the bleached coniferous wood kraft dissolving pulp fiber with a degree of polymerization DP of 210 and an α-cellulose content of 96.95% in step (2) was changed to a bleached broadleaf wood dissolving pulp fiber with a degree of polymerization DP of 613 and an α-cellulose content of 95.8%; the amount of dissolving pulp fiber was changed from 0.5 parts to 3 parts; the base paper in step (3) was changed from a commercially available 70g / m 2 Coated base paper changed to 180g / m 2 Uncoated white cardboard; coating method changed from one coat on a flat coater using a scraper bar to one coat using a scraper; coating amount changed from 0.2g / m 2 Changed to 2.0g / m 2 ; The soaking time in deionized water in step (4) was changed from 30S to 120S; the drying method was changed from drum drying to flat plate drying; the remaining operating steps were the same as in Example 1.
[0060] Example 6
[0061] A fully biodegradable ultra-high barrier antibacterial coating comprises the following components by mass percentage: 96.0% of regenerated cellulose and 4.0% of ZnO nanoparticles.
[0062] In the specific operation steps of the method of use, in addition to the ZnCl prepared in step (1), 2 The mass fraction of the solution was changed from 65% to 75%; the bleached softwood kraft dissolving pulp fiber with a DP of 210 and an α-cellulose content of 96.95% in step (2) was changed to a bleached bamboo dissolving pulp fiber with a DP of 326 and an α-cellulose content of 96.6%; the base paper in step (3) was changed from a commercially available 70 g / m 2 Coated base paper changed to 180g / m 2 For uncoated white cardboard, the coating method was changed from one-time coating on a flat coater using a scraper to coating using a spin coating method; the coating amount was changed from 0.2g / m 2 Changed to 1.0g / m 2 ; The base paper in step (3) is made of commercially available 70g / m 2 Coated base paper changed to 180g / m 2 For uncoated white cardboard, the coating method was changed from one-time coating on a flat coater using a scraper to coating using a spin coating method; the coating amount was changed from 0.2g / m 2 Changed to 1.0g / m 2 The remaining steps are the same as those in Example 1.
[0063] Example 7
[0064] A fully biodegradable ultra-high barrier antibacterial coating comprises the following components by mass percentage: 96.0% of regenerated cellulose and 4.0% of ZnO nanoparticles.
[0065] In the specific operation steps of the method of use, in addition to the ZnCl prepared in step (1), 2 The mass fraction of the solution was changed from 65% to 75%; the bleached softwood kraft dissolving pulp fiber with a degree of polymerization DP of 210 and an α-cellulose content of 96.95% in step (2) was changed to a cotton dissolving pulp fiber with a degree of polymerization DP of 478 and an α-cellulose content of 97.4%; the amount of dissolving pulp fiber was changed from 0.5 parts to 1.5 parts; the dissolution conditions were changed from 80°C and 15 min to 90°C and 10 min; the base paper in step (3) was changed from a commercially available 70 g / m 2 Coated base paper changed to 150g / m 2 Corrugated paper face paper; coating method changed from one-time coating on a flat coater using a scraper bar to coating using a scraper; coating amount changed from 0.2g / m 2 Changed to 3.0g / m 2; The soaking time in deionized water in step (4) was changed from 30S to 60S; the drying method was changed from drum drying to flat plate drying; the remaining operating steps were the same as in Example 1.
[0066] Example 8
[0067] A fully biodegradable ultra-high barrier antibacterial coating comprises the following components by mass percentage: 99.0% of regenerated cellulose and 1.0% of ZnO nanoparticles.
[0068] In the specific operation steps of the method of use, in addition to the ZnCl prepared in step (1), 2 The mass fraction of the solution was changed from 65% to 68%; the bleached softwood kraft dissolving pulp fiber with a DP of 210 and an α-cellulose content of 96.95% in step (2) was changed to a cotton dissolving pulp fiber with a DP of 338 and an α-cellulose content of 98.1%; the base paper in step (3) was changed from a commercially available 70 g / m 2 Coated base paper changed to 150g / m 2 Corrugated paper; coating amount from 0.2g / m 2 Changed to 1.0g / m 2 ; The remaining steps are the same as in Example 1.
[0069] In order to evaluate the antibacterial properties of paper-based materials with ultra-high barrier antibacterial coatings on the surface, the agar plate diffusion method was used with reference to GB / T20944.1-2007, and the antibacterial properties of the samples against Staphylococcus aureus and Escherichia coli were evaluated by measuring the width of the inhibition zone of each sample.
[0070] The paper-based material with the ultra-high barrier antibacterial coating on the surface obtained according to the steps of Examples 1 to 8 was tested for relevant barrier properties and antibacterial properties, and compared with the properties of two commercially available food packaging papers. The results are shown in the following table:
[0071]
[0072] From the data in the table, it can be seen that different coated base papers have different barrier properties and none of them have antibacterial properties. Compared with the base paper, the water absorption and air permeability of the paper-based materials with ultra-high barrier antibacterial coating on the surface obtained by Examples 1 to 8 are greatly reduced, and the water vapor and oxygen barrier properties are enhanced. At the same time, with the increase of ZnO content, the antibacterial properties of the paper-based materials are significantly improved. In addition, compared with two commercially available food packaging papers, the performance of the paper-based materials after using ultra-high barrier antibacterial coating is better than that of the two commercially available food packaging papers in all aspects.
[0073] The above preferred examples are only used to help explain the present invention, in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can better understand and use the present invention, and are not intended to limit the embodiments of the present invention. Obviously, various modifications and changes can be made according to the contents of this specification. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A fully biodegradable ultra-high barrier antibacterial coating, characterized by: The invention mainly comprises the following components by mass percentage: 95-99.5% of regenerated cellulose and 0.5-5% of ZnO nanoparticles; the regenerated cellulose is prepared by transferring dissolving pulp fibers to the surface of base paper through the dissolution-regeneration behavior in ZnCl2 solutions of different concentrations; the ZnO nanoparticles are Zn 2+ During the regeneration process of cellulose, ZnO nanoparticles are uniformly embedded in the regenerated cellulose membrane through in situ growth.
2. The fully biodegradable ultra-high barrier antibacterial coating according to claim 1, characterized in that: In the coating liquid - ZnCl2 / cellulose / water solution required for preparing regenerated cellulose, the cellulose is selected from one of bleached coniferous or hardwood kraft dissolving pulp, bleached bamboo dissolving pulp or cotton dissolving pulp, the degree of polymerization DP of the dissolving pulp fiber is 200-700, and the α-cellulose content is greater than 95%.
3. The fully biodegradable ultra-high barrier antibacterial coating according to claim 1, characterized in that: In the coating solution - ZnCl2 / cellulose / water solution required for preparing regenerated cellulose, ZnCl2 is analytically pure, the content of effective components is ≥98%, and the mass concentration of ZnCl2 is 65-80%.
4. The fully biodegradable ultra-high barrier antibacterial coating according to claim 1, characterized in that: In the coating solution for preparing regenerated cellulose - ZnCl2 / cellulose / water solution, the mass concentration of dissolved pulp fiber in the coating solution is 0.5-3.0%, and the coating amount of regenerated cellulose coating is 0.2-3 g / m 2 .
5. The fully biodegradable ultra-high barrier antibacterial coating according to claim 1, characterized in that: The particle size of the ZnO nanoparticles uniformly grown in situ and embedded in the regenerated cellulose membrane is 80-160 nm.
6. A method for using a fully biodegradable ultra-high barrier antibacterial coating, characterized in that: The following steps are involved: (1) Weigh 65-80 parts of ZnCl2 solid and 20-35 parts of deionized water and stir them thoroughly until ZnCl2 is completely dissolved to obtain a ZnCl2 solution; (2) weighing 0.5 to 3 parts of dissolving pulp fiber and mixing with the prepared ZnCl2 solution, rapidly stirring at a certain temperature until completely dissolved, and cooling to obtain a ZnCl2 / cellulose / water solution; (3) ZnCl2 / cellulose / water solution is transferred to different base paper surfaces by using a coating method selected from spin coating, rod coating and knife coating according to different mass fractions of ZnCl2; (4) After the base paper is coated with ZnCl2 / cellulose / water solution, it is allowed to stand for a certain period of time, and then immersed in deionized water for 30 to 120 seconds to regenerate and desalinate the dissolved cellulose pulp, and finally dried by drum drying or flat plate drying at a temperature of 85 to 105°C for a time of 10 to 30 minutes, thereby obtaining a paper-based material having an ultra-high barrier antibacterial coating on the surface.
Citation Information
Patent Citations
Method for preparing ZnO nanopowder from cellulose zinc chloride solution
CN106006709A
Degradable food packaging film with antibacterial function
CN108276598A
Zinc oxide / cellulose nanocrystalline composite material as well as preparation method and application thereof
CN108659266A
Cellulose film for blocking ink and preparation method thereof
CN108729299A
ZnO nanosheet regenerated cellulose film composite material and preparation method thereof
CN108889338A